MAẒĀHIR AS-SULŪK AL-INSĀNĪ TIJĀHA MAQṢAD ḤIFẒ AL-MĀL FĪ AL-KHIṬĀB AL-QUR’ĀNI - Radwan Jamal Yousef Elathrash; Angraini Binti Ramli (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2022)
This study aims to reveal various kinds of human behavior towards their properties and the ideal management of this property from the perspective of the Quran. This research also attempts to link the knowledge of the Quranic maqasid with the financial management carried out by humans to improve their contradictive behavior. By using qualitative methods with inductive descriptive approaches and various sources such as the Quran and its interpretations, journals, magazines, and classical literature, this research found that owning wealth does not contradict the concepts of zuhud and piety. The al-Quran displays human behaviors who manage their wealth well and make their wealth as a ware towards God. Multiple discourses about wealth in the Quran showed that the behavior of adoring wealth is natural and matches the Quranic nature, which adapted to human nature. The treasure and wealth itself belong to God, which humans naturally revere. Humans have different behavior when dealing with wealth. First, worldly behavior is not fair. Second, the behavior of miserly and miserly. Third, moderate behavior that has intelligent management in managing assets. Differences in human behavior in managing these assets are usually determined by their social environment.